Application of cerebrospinal fluid/serum albumin ratio in assessing blood - brain barrier permeability in children with drug-resistant epilepsy. - WANG, Yao; MA, Wei; CAI, Ao-jie; JIN, Pei-na; ZHUO, Zhi-hong; WANG, Huai-li (Chinese Journal of Contemporary Neurology & Neurosurgery, 2025)
The cerebrospinal fluid/serum albumin ratio (QAlb) serves as a critical indicator for assessing blood - brain barrier (BBB) permeability. This study aimed to assess BBB permeability in children with drug - resistant epilepsy (DRE) by calculating QAlb and to investigate its correlation with clinical characteristics, as well as its potential as a biological marker. Methods A total of 35 children diagnosed with DRE (epilepsy group) and 37 children with primary headache (control group) were admitted to The First Affiliated Hospital of Zhengzhou University between June 2018 and June 2023. QAlb values were derived from laboratory test results. Spearman rank correlation analysis was employed to explore the relationship between QAlb and variables such as disease duration, seizure type, seizure frequency, status epilepticus, and the number of antiepileptic seizure medicine (ASM). Results Compared with control group, the QAlb values were elevated [3.29 (2.39, 4.54) x 10³ vs. 2.15 (1.42, 2.59) x 10³; Z = 4.616, P = 0.000], and the incidence of BBB dysfunction was higher [28.57% (10/35) vs. 2.70% (1/37); χ² = 9.299, P = 0.002] in epilepsy group. Spearman rank correlation analysis indicated a positive correlation between QAlb and both seizure frequency (rs = 0.587, P = 0.000) and the number of ASM (rs = 0.367, P = 0.030) in children with DRE. Conclusions Some children with DRE exhibit BBB dysfunction. QAlb is positively correlated with seizure frequency and the number of ASM, suggesting its potential as a biological marker for identifying BBB dysfunction.